THE CALCULATION OF VALUE AT RISK USING VARIANCE COVARIANCE IN LQ-45 COMPANIES - Yoseva Maria Pujirahayu Sumaji (Jurnal Bisnis dan Keuangan, 2021)
The Government of Indonesia is trying to find some solutions to Indonesia's economic problems. One of the problems of Indonesia's economic growth is the lack of capital and correct calculation of capital risks, especially in stock investments can reduce the occurrence of various capital problems in accordance with the criteria required and obtained by 9 companies analyzed. The analytical method used in calculating market risk in stock investments in this study is variance covariance value at risk. This method is a risk measurement through the highest estimated losses over a period of time and assumed confidence levels. To prove the level of trust of the variance covariance value at risk method, analysis was conducted using back testing method. The results of this study show that the method of calculating variance covariance value at risk is the right and accurate method to calculate market risk from the company's stock.